IMPLEMENTATION OF LEGAL PROTECTION FOR SPECTATORS REGARDING THE CANCELLATION OF MUSIC FESTIVAL BY THE ORGANIZERS IN SURABAYA AREA - Putri, Shafanisa Aurelia; Wahyudi, Eko (Universitas Islam Balitar, 2024)
According to Law No. 8 of 1999, in music festival performances, the position of the audience is as consumers and the position of the organizers is as business actors. In conducting business relationships, organizers are required to protect consumers from all kinds of event problems, including from cancellations. However, in practice, legal protection for spectators has not been implemented optimally. In Surabaya, there were three music events which were canceled at the same time. One of the three has fulfilled the legal protection. The method used is empirical juridical with analytical descriptive method and uses primary and secondary data sources. The results of the research found that the implementation of legal protection for spectators for the cancellation of music festivals in the Surabaya area has been going well, but the benefits for the audience have not been maximized. Obstacles that are felt in its implementation are the lack of funds from the organizers and